Prevalence of long-term right ventricular dysfunction after acute pulmonary embolism: a systematic review and meta-analysisResearch in context - Dingyi Wang; Guohui Fan; Xiaomeng Zhang; Linfeng Xi; Yinong Chen; Aili Li; Zhenguo Zhai (EClinicalMedicine, 2023)
Summary: Background: Right ventricular dysfunction (RVD) is associated with adverse outcomes of acute pulmonary embolism (PE). However, there are no studies describing the long-term, full-spectrum right ventricular parameters on morphology, pressure and function at certain follow-up time points after PE onset. More exploration of right ventricular function would provide useful clues for long-term management of patients with PE. Methods: For this systematic review and meta-analysis, we completed a literature search in Pubmed, EMBASE and WebofScience (from Jan 1st, 1998 to April 20th, 2023). Studies of patients with acute PE followed-up longer than 3 months with right ventricle assessment and written in English-language were included. Right ventricular function was assessed by either echocardiography or computed tomographic pulmonary angiography (CTPA). The primary outcome was structural and functional parameters of the right ventricle, and the secondary outcomes were functional assessments [New York Heart Association (NYHA) functional classification and 6-min walk test distance (6 MWD)], at each follow-up time points. Random effect meta-analyses were performed using R software (PROSPERO: CRD42023433332). Findings: A total of 33 studies (3920 patients) were included in the final analysis. The 3-month, 6-month and 1-year prevalence of right ventricular dysfunction (RVD) was 0.34 [95% confidence interval (CI) 0.21–0.48, I2 = 96%], 0.26 (95% CI 0.17–0.36, I2 = 93%) and 0.34 (95% CI 0.19–0.48, I2 = 94%), respectively. Pooled tricuspid annulus plane systolic excursion (TAPSE), right ventricular to left ventricular diameter (RV/LV) ratio and pulmonary artery systolic pressure (PASP) at 1-year was 21.80 mm (95% CI 20.08–23.52, I2 = 93%), 0.64 (95% CI 0.48–0.81, I2 = 92%) and 27.33 mmHg (95% CI 18.88–35.78) (I2 = 96%), respectively. The proportion of NYHA III–IV was 0.06 (95% CI 0.0–0.12) and the pooled 6 MWD was 462.98 m (95% CI 447.55–478.41) over 1 year. Patients treated with thrombolysis had lower prevalence of RVD (1-year 0.17 and 0.07 in systemic thrombolysis and catheter-directed thrombolysis, respectively) than those treated with anticoagulation therapy alone (1-year 0.24) but the pooled risk ratio (RR) was not statistically significant. Interpretation: Although the conclusion of this study may be limited by its high heterogeneity from varied study designs, inclusion criteria and definition of RVD of each study, our findings suggested that persistent RVD and functional impairment were of considerable high prevalence during long-term follow-up after acute PE. Treatment strategy may influence the prevalence of long-term RVD. Funding: This study is supported by CAMS Innovation Fund for Medical Sciences (CIFMS) (2021-I2M-1-061). The National Key Research and Development Program of China (2016YFC0905600). National High Level Hospital Clinical Research Funding (2022-NHLHCRF-LX-01-02-03). CAMS Institute of Respiratory Medicine Grant for Young Scholars (2023-ZF-8).